Design Rules of a Sulfur Redox Electrocatalyst for Lithium–Sulfur Batteries. Issue 14 (24th February 2022) - Wang, Li; Hua, Wuxing; Wan, Xiang; Feng, Ze; Hu, Zhonghao; Li, Huan; Niu, Juntao; Wang, Linxia; Wang, Ansheng; Liu, Jieyu; Lang, Xiuyao; Wang, Geng; et al.
Abstract: Seeking an electrochemical catalyst to accelerate the liquid‐to‐solid conversion of soluble lithium polysulfides to insoluble products is crucial to inhibit the shuttle effect in lithium–sulfur (Li–S) batteries and thus increase their practical energy density. Mn‐based mullite (SmMn2 O5 ) is used as a model catalyst for the sulfur redox reaction to show how the design rules involving lattice matching and 3d‐orbital selection improve catalyst performance. Theoretical simulation shows that the positions of Mn and O active sites on the (001) surface are a good match with those of Li and S atoms in polysulfides, resulting in their tight anchoring to each other. Fundamentally, d z 2 and d x 2 − y 2 around the Fermi level are found to be crucial for strongly coupling with the p‐orbitals of the polysulfides and thus decreasing the redox overpotential. Following the theoretical calculation, SmMn2 O5 catalyst is synthesized and used as an interlayer in a Li–S battery. The resulted battery has a high cycling stability over 1500 cycles at 0.5 C and more promisingly a high areal capacity of 7.5 mAh cm −2 is achieved with a sulfur loading of ≈5.6 mg cm −2 under the condition of a low electrolyte/sulfur (E/S) value ≈4.6 µL mg −1 . Abstract : Lattice matching and 3d‐orbital selection are proposed as two rules for the rational design of sulfur redox electrocatalysts. The former promotes the tight anchoring of polysulfides onto the SmMn2 O5 catalyst, while the latter reduces the overpotential of the sulfur redox reaction, fundamentally accelerating the conversion of liquid‐phase polysulfides to solid‐phase discharge product and thus suppressing the shuttling.